Cases and Materials on Fundamentals of Partnership Taxation (Book). - Hendrickson, Harvey S.; Auster, Rolf (The Accounting Review, 1986)
Reviews the book "Cases and Materials on Fundamentals of Partnership Taxation," by Stephen A. Lind, Stephen Schwaritz, Daniel J. Lathrope and Joshua D. Rosenberg.